2022
DOI: 10.1097/acm.0000000000004799
|View full text |Cite
|
Sign up to set email alerts
|

“Finding My Piece in That Puzzle”: A Qualitative Study Exploring How Medical Students at Four U.S. Schools Envision Their Future Professional Identity in Relation to Health Systems

Abstract: PurposeHealth systems science (HSS) curricula equip future physicians to improve patient, population, and health systems outcomes (i.e., to become "systems citizens"), but the degree to which medical students internalize this conception of the physician role remains unclear. This study aimed to explore how students envision their future professional identity in relation to the system and identify experiences relevant to this aspect of identity formation. MethodBetween December 2018 and September 2019, authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 78 publications
(132 reference statements)
1
2
0
Order By: Relevance
“…Indeed, one recent study used qualitative techniques to examine how medical students "envision their future professional identity in relation to the system" and found that there are a variety of factors that contribute to student views on system citizenship, including the fact that some students were "more likely to view systems expertise as distributed within interprofessional teams". 31 This study finding appears to be congruent with the fact that M4 students in our study were more likely to agree that other health care professionals can sometimes lead a clinical team. The construct of system citizenship is not yet well-defined and is therefore challenging to assess.…”
Section: Dovepresssupporting
confidence: 86%
See 2 more Smart Citations
“…Indeed, one recent study used qualitative techniques to examine how medical students "envision their future professional identity in relation to the system" and found that there are a variety of factors that contribute to student views on system citizenship, including the fact that some students were "more likely to view systems expertise as distributed within interprofessional teams". 31 This study finding appears to be congruent with the fact that M4 students in our study were more likely to agree that other health care professionals can sometimes lead a clinical team. The construct of system citizenship is not yet well-defined and is therefore challenging to assess.…”
Section: Dovepresssupporting
confidence: 86%
“…This possibility is consistent with a qualitative study wherein “influential experiences before medical school” were found to have an impact on the aspirations of medical students related to future involvement in efforts to impact health systems. 31 Whether these experiences prior to medical school could also impact the scores of a given group of medical students on the HSS subject exam is an intriguing question. Although our study protocol did not allow us to examine these class characteristics, this would seem to be an important consideration for future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation